Genetic variability and association analysis in barnyard millet (Echinochloa frumentaceae) under multiple environments - M. Sudhir Deepak1, C. Vanniarajan2, R. Chandirakala3, R. Renuka1 and S. Kanchana4 (Electronic Journal of Plant Breeding, 2023)
Barnyard millet is an important short duration nutricereal. A study was conducted to measure the pooled variation and association among yield and its component traits in 27 barnyard millet genotypes raised in six locations. The experiment was raised in RBD with three replications. The pooled ANOVA revealed significant difference between genotypes. High PCV and GCV were recorded for number of productive tillers, flag leaf length, flag leaf breadth, single ear head weight, fodder yield per plant, grain yield per plant. Except for days to maturity, all attributes were governed by additive gene effects, which was evident for high heritability and genetic advance values. Correlation studies exhibited significant positive relationship of grain yield with panicle length, single ear head weight, thousand grain weight and fodder yield per plant. Results of path coefficient analysis indicated that single ear head weight and days to first flowering had direct effect towards grain yield. Thus, by using single ear head weight and days to first flowering as selection indices, grain yield of barnyard millet could be augmented.